Straight roads into nowhere – obvious and not-so-obvious biological models for ferrophobic surfaces - Konrad, Wilfried; Neinhuis, Christoph; Roth-Nebelsick, Anita (Beilstein Journal of Nanotechnology, 2022)
There are currently efforts to improve strategies for biomimetic approaches, to identify pitfalls and to provide recommendations for a successful biomimetic work flow. In this contribution, a case study of a concrete biomimetic project is described that started with a posed technical problem for which seemingly obvious biological models exist. The technical problem was to devise a ferrophobic surface that prevents the contact between the copper surface of a tuyère (a water cooled aeration pipe within a blast furnace) and liquid iron. Therefore, biological external surfaces that strongly repel liquids appeared to be suitable, particularly the hair cover of the water fern Salvinia molesta and the surface of Collembola (an arthropod group). It turned out, however, that it was not feasible to realise the functional structures of both biological models for the tuyère problem. Instead, a seemingly not obvious biological model was identified, namely micropores within the cell walls of water-transporting conduits of plants that connect the conduits to a three-dimensional flow network. These specially shaped pores are assumed to be able to create stable air bodies, which support the refilling of embolised conduits. By adopting the shape of these micropores, a successful prototype for a ferrophobic copper surface repelling liquid iron could be devised. This case study illustrates that straight road maps from technical problems to obvious biological models are no guarantee for success, and that it is difficult to arrive at a formalised biomimetic working scheme. Rather, a broad understanding of biological function and its complexity is beneficial.
Keywords: air-retaining interfaces; bioinspiration; biomimetics; biomimicry; blast furnace; Collembola; gas/liquid interfaces; interfacial effects; persistant air layers; pits; Salvinia molesta; surfaces; tuyère failure; water transport in plants; xylem; Young–Laplace equation